The European Union's service directive: Contrasting ex ante estimates with empirical evidence - Bianka Dettmer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
One of the top priorities to improve the European Union's growth performance is the creation ofsingle market for services. The directive on services adopted by the Parliament and the Council by the end of 2006 aims at removing barriers to the free movement of service providers on the internal market. Previous studies quantified ex ante sizable effects of implementing the directive in its original form. This paper is a first attempt to evaluate ex post the trade effects induced by a directive - which excludes the country-of-origin principle - by performing a difference-in-difference-(in-differences) estimator on a sample of EU- and non-EU countries in the period 2004 to 2010. We account for non-tariff trade barriers and the endogeneity of regional trade agreements and find that deregulations foster a deeper integration of the new member states into the European value-added-chain and promote business service exports from third countries towards the EU. The reorientation of the new members is in turn associated with declining intra-EU10 business intensities while leaving business trade among the entire members largely unaffected.
Keywords: F12; F15; L84; 330; service directive; non-tariff barriers; outsourcing; internal market; EU; Internationaler Dienstleistungsverkehr; Dienstleistungssektor; EU-Binnenmarkt; Wirkungsanalyse; Outsourcing; Außenhandelseffekt; EU-Staaten